(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
Based on summarizing and processing the multiyear test data on desalination and agricultural developing of solonetz-solonchak soils against a background of horizontal drains (the key terrain is located in Ararat Valley), empirical formulae have been derived that allow to calculate the horizontal drain parameters. It greatly reduces the financial expenses necessary for exploration work and implementation of experimental filtration research aiming at determination of filtration and capacity parameters of the grounds.